Optimal Measurements of Surface Water Pollution-Case Study on Southern Part of Romania - Florescu, D.; Ionete, R.E.; Iordache, A.; Horj, E.; Stefanescu, I.; Culea, M. (Asian Journal of Chemistry, 2011)
In this research, some surface waters originating from southern of Romania (Arges, Olt and Jiu rivers) were studied in order to assess the effects of atrophic pollution, based on analyses performed in the springtime of 2010. Water quality indicators like pH, conductivity, turbidity and dissolved oxygen, chloride, calcium and fluorine ions, nitrates and ammonia ions, total organic carbon and heavy metals content have been analyzed in three different points/rivers thereby before, after and from a main city on the rivers. The measured parameters in analyzed water samples showed slight variations depending on location, the water quality for all the three investigated rivers being affected by both natural and anthropogenic factors.